The Effects of Managerial Finance on Growth of Business: Evidence from Akwa Ibom State, Nigeria - Ekpo , Ntiedo B.; Etukafia , NseAbasi I.; Acha , Ikechukwu A.; Udoidem , John; Asogwa , Ikenna Elias (Current Topics on Business, Economics and Finance Vol. 5, 2023)
This chapter investigates the relationship between selected managerial finance functions and business growth. The motivation was the commonly heard argument that poor attitudes to managerial finance are the key factor in the high failure rate of business in different countries, including Nigeria. A survey research design was adopted to obtain data from 105 businesses operating in Akwa Ibom State - Nigeria and analyzed using Pearson’s Product Moment Correlation model. The findings indicate that all of the managerial functions chosen for the study are strongly correlated with growth, albeit at varying degrees of significance. The findings imply that, given the diversity and specialized nature of managerial finance, every aspect of management relating to financial resources should be treated seriously in order to ensure long-term sustainable business growth.